Examining the role of the hedgehog pathway in wound healing and exploring various therapeutics to rescue delayed wounds - Tang, Job Zheng Qiang (Nanyang Technological University, 2021)
This thesis is organised into two parts. The first part of the thesis investigated the role of the Hedgehog pathway in dermal fibroblast functions in wound healing. Smoothened (Smo) conditional knockout mice were used as the experimental model while Smoflox/flox mice were used as the experimental control. A series of molecular, immunological, histological and macroscopic analyses were performed. Although Smo was successfully knocked out, the mice model demonstrated delayed wound-like features, intra-variability in wound healing and the Hh pathway remained partially active. The combination of these factors together with the small sample size may account for the inconclusive experimental results that were obtained in the study. Nevertheless, this thesis has shown that the Smo conditional knockout mice and Smoflox/flox may not be a suitable animal model to investigate the role of the Hh pathway in dermal fibroblast functions during wound healing. The second part of the thesis evaluated the therapeutic efficacy of D+Q in combination with either tonabersat or antisense oligodeoxynucleotides that were specific to Connexin 43 on a perturbed model of wound healing. Although the perturbed wound model in rats was successfully generated, the drug treatment results obtained from the study were inconclusive. Factors such as the lack of statistical power due to the small sample size and other methodological challenges may need to be considered in future studies. Nevertheless, this study highlights several trends that may warrant further research.